Body image in the primary school a self esteem approach to building body confidence - Hutchinson, Nicky; Calland, Chris (Routledge, Taylor & Francis Group, 2020)
"Young people's body image is a growing problem that has become even more of an issue in recent years. This updated second edition of Body Image in the Primary School recognises this as a concern for younger children that needs to be addresses at an early age and examines some of the pressures that young people face. It presents a clear, easy to use scheme of work to support emotional literacy and PSHE throughout the primary years and into the first years of secondary school. This scheme of work will help young people to develop resilience to the pressures of modern society and develop a healthy body image, whilst supporting their parents and carers for years to come"--